2001
DOI: 10.1007/s004670100634
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme gene polymorphism in primary vesicoureteral reflux

Abstract: We studied the insertion/deletion (I/D) polymorphism of the angiotensin converting enzyme (ACE) gene in 78 patients with primary vesicoureteral reflux (VUR), and examined renal function by dimercaptosuccinate (DMSA) renoscintigraphy and diethylenetriamine-penta-acetic acid (DTPA) renogram in each genotype. Patients were classified into three genotypes according to the ACE gene I/D polymorphisms: 32 in II genotype, 36 in ID, and 10 in DD. The incidence of presumably congenital unilateral small kidneys was high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 26 publications
0
24
0
2
Order By: Relevance
“…[28] Distribution of the renin-angiotensin system polymorphism in children with VUR is well-studied, and its effect on renal scarring is of interest. [2][3][4]8,20] However, reports about this subject are contradictory. Generally, the ACE polymorphism is the most commonly studied and accepted genetic effect in VUR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Distribution of the renin-angiotensin system polymorphism in children with VUR is well-studied, and its effect on renal scarring is of interest. [2][3][4]8,20] However, reports about this subject are contradictory. Generally, the ACE polymorphism is the most commonly studied and accepted genetic effect in VUR.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Several polymorphisms of the genes encoding the renin-angiotensin system (RAS) have been studied in the pathogenesis of this malformation, especially the AT2 polymorphism. [1,2] ATR1 A1166C and ATR2 C3123A have been found to be related with primary VUR; in addition, ATR2 C3123A and AGT M235T polymorphisms have been strongly related with increased risk for the development of chronic renal failure in the general population. [3][4][5] A deletion (D) or insertion (I) of a 287-base pair (bp) fragment at intron 16 of the ACE gene has been shown to be involved in the modulation of circulating and tissue ACE activity.…”
Section: Introductionmentioning
confidence: 99%
“…these findings have been supported by two further studies, one of which also reported an association between the D allele of ACE to small congenital kidneys with refluxing ureters in patients with primary vur, and to the progression of reflux nephropathy. 116,117 Contrastingly, these data could not be reproduced in studies by Park et al 118 and Yoneda and colleagues, 119 who drew the opposite conclusions.…”
Section: Pax2mentioning
confidence: 89%
“…In numerous studies, the importance of genetic predisposition to renal scarring was emphasized. An association between polymorphism of angiotensin-converting enzyme gene and renal scarring was demonstrated (Haszon et al, 2002;Hohenfellner et al, 1999;Ohtomo et al, 2001;Ozen et al, 1999;Pardo et al, 2003). Similarly, polymorphism of transforming growth factor gene (Kowalewska-Pietrzak et al, 2008;Hussein et al, 2010) and polymorphism of vascular endothelium growth factor gene (Hussein et al, 2010) had impact on severity of renal scarring.…”
Section: Urinary Tract Infections 310mentioning
confidence: 98%
“…The D allele of ACE gene polymorphism was associated with higher converting enzyme activity and thus higher concentration of a n g i o t e n s i n I I i n p l a s m a a n d t i s s u e s . T h i s r e s u l t e d i n m o r e r a p i d d e v e l o p m e n t a n d progression of RN (Haszon et al, 2002;Hohenfellner et al, 1999;Ohtomo et al, 2001;Ozen et al, 1999). Some studies questioned the significance of ACE gene polymorphism as an independent risk factor for the development and progression of RN (Dudley et al, 2002;Pardo et al, 2003).…”
Section: Reflux Nephropathymentioning
confidence: 99%